POSSIBILITIES OF USING CHINESE EXPERIENCE IN COMBATING POVERTY IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This research explores the potential application of China’s poverty alleviation strategies in Uzbekistan, a nation facing significant socio-economic challenges. Over the past few decades, China has successfully lifted millions out of poverty through a combination of targeted economic reforms, infrastructure development, and social welfare programs. This study examines key elements of the Chinese model, including rural development initiatives, microfinance schemes, and vocational training programs that have proven effective in enhancing livelihoods. By analyzing Uzbekistan’s current socio-economic landscape and existing poverty alleviation efforts, this research identifies opportunities for adopting similar strategies tailored to local contexts. The paper also discusses potential barriers to implementation, such as governance issues, cultural differences, and resource constraints. Furthermore, it emphasizes the importance of stakeholder engagement and international cooperation in fostering sustainable development. Ultimately, this research aims to provide actionable recommendations for policymakers in Uzbekistan to enhance their poverty reduction efforts by leveraging successful practices from China while considering unique national circumstances.